Application of the problem-based learning (PBL) methodology in the study of pathophysiology as a theoretical basis for the formation of clinical thinking - Vasylenko, G. V.; Василенко, Гліб Володимирович (Chicago : BoScience Publisher, 2023)
Clinical thinking is an important aspect of medical education that reflects a doctor's ability to make decisions and diagnoses. Clinical thinking allows you to make both logical and non-standard decisions in clinical practice and look at the diagnosis from different angles, that is, to make decisions under conditions of uncertainty.
Keywords: pathophysiology; clinical thinking; treatment tactics; basic link; simulation-based education; pharmacotherapy; disease prevention; small groups of students